RESULTS OF PASSENGER RESOURCES EXAMINATIONS IN KYZYL CITY OF THE TYVA REPUBLIC - Ch. D. Shavyraa (Вестник СибАДИ, 2018)
Introduction. The paper considers the results of surveys taking into account the efficiency increase of passenger traffic in a small town. The need to regulate the work of carriers of various ownership forms, taking into account the characteristics of urban routes, determines the relevance of the research in this area. Therefore, the purpose of the survey is to clarify the total size of the movement of the zones and the city as a whole for the further projects’ development of the road network planning and for the passenger traffic development.Materials and methods. The paper considers alternatives to passenger surveys, i.e. application of the most optimal variants of the transportation plan. The characteristics of the route and load on the routes of Kyzyl are also illustrated. The author uses the methodology of surveying the population transport needs in a small town, in particular, the counting of passengers.Results. As a result, the author conducts the survey of passenger traffic, taking into account the city specific. The characteristics of the route and the load on the routes of Kyzyl are studied. It is important to use the methodology of the transport needs and transport services for population in a small town.Discussion and conclusions. On the basis of the conducted surveys of passenger traffic, the average hourly volume of transportation on routes is revealed and the unevenness of traffic volume is calculated.